Application of fracture criteria to the simulation of BOP ram shearing - Zhu, Lei (2020)
A subsea blowout preventer (BOP) stack is of great importance for the safety of offshore oil and gas drilling operations. The shear ram BOP provides the last defense for blowout protection. Fail to cut the drill pipe or isolate the well may induce disaster damage on humans and facilities, as it happened in the case of the Macondo accident. A common approach to help to evaluate the shear capacity of the BOP ram is the finite element technique, but the accuracy is still a challenge due to the difficulty of selecting and applying a proper fracture criterion. The objective of this thesis is to provide a thorough approach to apply fracture criteria for the simulation of BOP ram shearing. The following fracture criteria, CrashFEM, Johnson-Cook, and Modified Mohr-Coulomb, are applied, and the obtained results are compared. The TRIP 690 experimental data are used to derive the fracture parameters for all criteria, and a modified calibration approach, specifically for CrashFEM criterion, is proposed based on a standard tensile test of S135 drill pipe material, thus enabling the practical application of provided fracture criterion. To verify the numerical model combined with the fracture criterion, a full-scale BOP ram shearing experiment is conducted. Reliable numerical models with refined mesh are built according to the loading and boundary conditions in the experiment. The shearing pressure curve is firstly compared with the simulated pressure curve. The result shows that the correlation between numerical and experimental results is consistent. A case study is conducted to investigate the shear efficiency for different ram blades. The proposed model is successfully applied to analyze the shear efficiency of each ram design.